Pengembangan LKPD Digital Berbasis Realistic Mathematics Education Untuk Meningkatkan Kemampuan Literasi Matematis Siswa - Hura, Paguita (Sepren, 2025)
This research aims to develop and assess the quality of a digital student worksheet (LKPD) based on the Realistic Mathematics Education (RME) approach in terms of validity, practicality, effectiveness, and its impact on students’ mathematical literacy skills. The study employs the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) and involves seventh-grade students (Class VII-9) at SMP Negeri 29 Medan as research subjects. The instruments used include questionnaires and tests. The research findings indicate that: (1) the digital LKPD is considered valid, with validation scores of 3.96 from material experts (categorized as very valid) and 4.11 from media experts (categorized as valid); (2) the LKPD is rated as highly practical by teachers (87.27%) and students (90.20%); (3) the LKPD is effective, as evidenced by: (a) a classical completeness rate of 90.63%; (b) individual learning objective achievement rate of 83.94%; (c) a positive student response rate of 89.17%; and (d) an increase in the average pretest score from 41.41 to 83.94 for mathematical literacy indicators. The overall average literacy score improved from 43.06 (pretest) to 75.00 (posttest), with an N-Gain score of 0.72, classified as high. These findings indicate that the RME-based digital LKPD is feasible and effective for enhancing students' mathematical literacy skills at the junior high school level.